Investigation of extraesophageal gastroesophageal reflux disease - Tsoukali, Emmanouela (Hellenic Society of Gastroenterology, 2013)
The most common extraesophageal manifestations of gastroesophageal reflux disease (GERD) include chronic cough, asthma and laryngitis. There are two mechanisms proposed to explain extraesophageal syndromes caused by GERD. The first one is a direct way via irritation and/or microaspiration and the second one is an indirect, vagally mediated way. The investigation of extraesophageal manifestations of GERD is difficult and the empirical therapy with proton pump inhibitors usually double dose for at least three months is still the most common approach.